Experiência musical (en)cadeia canto, dança e poesia: encontro com mulheres no contexto prisional - Diniz, Margarete Hiromi Kishi (2023)
In this thesis, it was sought to understand the humanizing possibilities of Music Education in the female prison context through musical practices made with bodily experiences and sensory experiences. The main objective was to identify possible potentialities of Music Education experienced by women in the Female Public Prison of Cáceres, Mato Grosso, Brazil. For that, the following specific objectives were outlined: to carry out a Music Education experience with women in situation of deprivation of liberty; to analyze the perceptions of the Women of the Research after their musical experiences, through the production of data from the information collected from the Questionnaires, the Field Diaries, the records in the “Cadernos de Guardados” [Keeper Notebooks], the chart of the State of Mind Thermometer and the unstructured interviews; to analyze the results of the empirical research, in order to reflect on the potential of Music Education in the analyzed prison context. The research, of a qualitative nature, had as a methodological approach the action research that had the contributions of Thiollent (1986), Barbier (2002a, 2002b) and Tripp (2005). The content analysis proposed by Bardin (2016) was used. The theoretical contribution included three pillars: 1) Prisons, with the concept of disciplining the docile body (FOUCAULT, 2013); of “total institutions” and stigma (GOFFMAN, 1974); and the sociology of punishment (WACQUANT, 2003, 2011); 2) Curricular Justice and its three dimensions: Knowledge, Care and Democratic Coexistence, based on Ponce (2016, 2018); and 3) Music Education as a social function, based on the thoughts of Souza (2003, 2004, 2008, 2014), A.-M. Green (1987) and L. Green (1996). The musical practices experienced were inspired by the active methodology approach in Music Education and the Interdisciplinarity of Fazenda (1995, 2003, 2011). The results point out that the women, when participating in the musical experiences, were able to rescue their joy by expressing what they feel and think with their body and their voice, rediscovering themselves as more powerful beings, increasing their self-esteem and self-confidence, strengthening their social and affective-emotional relationships. A process of humanization was evidenced as a result of the musical experience lived in the context of the prison system